2016
DOI: 10.1108/h-09-2014-0062
|View full text |Cite
|
Sign up to set email alerts
|

Unique aspects of the Islamic microfinance financing process

Abstract: Purpose: This paper aims to highlight on the unique aspects of Islamic microfinance based on the experience of Baitul Maal Wa Tamwil (BMT) in Indonesia. Design/methodology/approach: It adopts the content analysis approach and focuses on three phases of financing, namely, pre-financing, financing and post-financing using coding and model buildings. Data are collected through in-depth interview with a sample of representatives of BMTs that offer product based on Islamic principle for the poor located in Jakarta,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…There are also research topics, specific to certain regions, which are not associated with any SI present in the MIX Market database. We found that in the financial dimension, Islamic banking is a relevant issue in EAP and South Asia [40,95,96], and the financial crisis and market saturation [97][98][99] are relevant issues in the LAC region; environmental issues like climate change [100,101], natural disasters [102] or the 2004 tsunami [103][104][105] are significant in Asia, and in the case of governance, the specific aspects investigated and not reported by region are corruption in South Asia [69,106], and accountability in Africa [107,108]. Concern for regulation is broadly researched and extends to all regions [28,109,110], among others.…”
Section: Divergencesmentioning
confidence: 80%
See 2 more Smart Citations
“…There are also research topics, specific to certain regions, which are not associated with any SI present in the MIX Market database. We found that in the financial dimension, Islamic banking is a relevant issue in EAP and South Asia [40,95,96], and the financial crisis and market saturation [97][98][99] are relevant issues in the LAC region; environmental issues like climate change [100,101], natural disasters [102] or the 2004 tsunami [103][104][105] are significant in Asia, and in the case of governance, the specific aspects investigated and not reported by region are corruption in South Asia [69,106], and accountability in Africa [107,108]. Concern for regulation is broadly researched and extends to all regions [28,109,110], among others.…”
Section: Divergencesmentioning
confidence: 80%
“…(1) When considering the individualistic-collectivistic dimension, microfinance research establishes a positive relationship in those societies more collectivist [40,41] and with higher levels of trust [41,42]. These circumstances are directly related to financial facts like considering self-help groups when granting funding, and in turn derived from social issues such as possible access to health services [43,44] or the consequences of this kind of repayment model, especially in the case of women [45,46].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dusuki (2008) contends that building skills through social intermediation are important for the success of Islamic microfinance. If support is extended during the pre-financing stage, financing stage and post-financing stage, then there is a greater chance of impactful results (Wulandari et al , 2016).…”
Section: Ensuring “Financial Sustainability” For the Programmementioning
confidence: 99%
“…This shows that developed countries have steeper diffusion curves on the Internet and shorter time lags than developing countries. Wulandari, et.al., (2016) 22 , highlighting the unique aspects of Islamic microfinance based on the experience of Baitul Maal Wa Tamwil (BMT) in Indonesia, Findings of the proposed Model include the characteristics of the poor in pre-financing, financing and post-microfinance products to be used as a reference for policy makers. This paper also found that each region has unique product preferences depending on the characteristics of the poor.…”
Section: Previous Studiesmentioning
confidence: 99%